The importance of familial risk factors in children with ADHD: direct and indirect effects of family adversity, parental psychopathology and parenting practices on externalizing symptoms - Lea Teresa Jendreizik; Christopher Hautmann; Elena von Wirth; Christina Dose; Ann-Kathrin Thöne; Anne-Katrin Treier; Tobias Banaschewski; Katja Becker; Daniel Brandeis; Julia Geissler; Johannes Hebebrand; Sarah Hohmann; et al. (BMC, 2022)
Abstract Background Children experiencing unfavorable family circumstances have an increased risk of developing externalizing symptoms. The present study examines the direct, indirect and total effects of family adversity, parental psychopathology, and positive and negative parenting practices on symptoms of attention-deficit/hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) in children with ADHD. Methods Data from 555 children (M = 8.9 years old, 80.5% boys) who participated in a multicenter study on the treatment of ADHD (ESCAschool) were analyzed using structural equation modeling (SEM). Results The SEM analyses revealed that (a) family adversity and parental psychopathology are associated with both child ADHD and ODD symptoms while negative parenting practices are only related to child ODD symptoms; (b) family adversity is only indirectly associated with child ADHD and ODD symptoms, via parental psychopathology and negative parenting practices; (c) the detrimental effect of negative parenting practices on child ADHD and ODD symptoms is stronger in girls than in boys (multi-sample SEM); (d) there are no significant associations between positive parenting practices and child ADHD or ODD symptoms. Conclusions Family adversity, parental psychopathology, and negative parenting practices should be routinely assessed by clinicians and considered in treatment planning. Trial registration (18th December 2015): German Clinical Trials Register (DRKS) DRKS00008973.